2005
DOI: 10.1370/afm.262
|View full text |Cite
|
Sign up to set email alerts
|

Office-Based Unsedated Ultrathin Esophagoscopy in a Primary Care Setting

Abstract: PURPOSE Gastroesophageal refl ux disease is common and with time may be complicated by Barrett's esophagus and esophageal adenocarcinoma. Upper gastrointestinal endoscopy, including esophagoscopy, is the procedure of choice to diagnose Barrett's esophagus and other esophageal disease. The use of unsedated ultrathin esophagoscopy (UUE) has been reported by gastroenterologists in specialized endoscopy units and otolaryngologists in outpatient otolaryngology offi ces, but UUE has not been previously described in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Thus, several endoscopy techniques have recently been developed as alternatives and less invasive diagnostic tools for evaluating GERD and esophageal varices [12][13][14][15][16]20] . Here, in this study we have shown that unsedated esophagoscopy using a novel disposable transnasal esophagoscope (E.G.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, several endoscopy techniques have recently been developed as alternatives and less invasive diagnostic tools for evaluating GERD and esophageal varices [12][13][14][15][16]20] . Here, in this study we have shown that unsedated esophagoscopy using a novel disposable transnasal esophagoscope (E.G.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that ECE is safe and has an acceptable accuracy for the evaluation of esophageal varices and can be used as an alternative to EGD for the screening of portal hypertension, especially in patients unable or unwilling to undergo EGD [7,9] . Unsedated small-caliber transnasal esophagoscopy offers the possibility of efficient and accurate endoscopic assessment of the esophagus, with less cost and fewer risks compared with sedated upper endoscopy, and can be used as a method to screen for esophageal disease in a primary care population [11][12][13][14][15] . Recently, Chung et al [16] , in a case series study, reported the use of a novel disposable transnasal esophagoscope, the E.G.…”
Section: Introductionmentioning
confidence: 99%
“…After they provided informed consent, patients were anesthetized using a method we have described previously. 9 The procedures in this study were performed by or supervised by the lead author (TW) between February 2002 and April 2008 using either XEF-140Y1 gastrointestinal videoscope or ENF-P3 laryngoscope (Olympus America, Inc., Melville, NY). The XEF-140Y1 has an outer diameter of 4.0 mm at the insertion tube, a working length of 600 mm, a bending section that can be maneuvered upward 180 degrees and downward 90 degrees (with no right or left deflection), and a field of view of 120 degrees.…”
Section: Methodsmentioning
confidence: 99%
“…18,19 Unsedated ultrathin transnasal endoscopy (TNE) can be feasible, well-tolerated, safe, and accurate in evaluating the esophagus. [20][21][22][23][24][25][26][27] A recent study suggested that it could be used accurately for BE screening and surveillance. 26 However, the applicability of this study may be limited because the level of agreement between the SE and TNE was only moderate ( ϭ 0.591) for diagnosing BE.…”
mentioning
confidence: 99%